Negotiating the Complexities of Mothering: An Autoethnography - Calica, Melissa Prudencio (CV. Literasi Indonesia, 2023)
This research delved into the nuanced experiences of a first-time mother. Using the lens of autoethnography, she provided an elaborate narrative of how she navigated the complex social role of motherhood. The study highlighted how she negotiated the inherent contradictions within the motherhood experience as both liberating and restrictive. The exploration focused on uncovering the intricate web of social and cultural influences that shaped and influenced her mothering practices, particularly within the context of the good mother ideology and the prevailing culture of intensive mothering which imposes idealized standards of motherhood. A significant emphasis of the study was made on her dual role as a mother and a teacher, examining her roles as a mediator of nature and culture. The autoethnography further unveiled the intricacies of conflicts, contradictions, and complexities that emerged from her interactions with significant others and society in general. The implication of this research is multifaceted and extends beyond the individual narrative of the first-time mother, offering a nuanced analysis of the intricate connection between personal agency and external pressures in the realm of motherhood. The examination of these intricacies calls for a reevaluation of the expectations and standards surrounding motherhood. By highlighting the impacts of social and cultural factors on mothering practices, this study emphasizes the need to critically assess and redefine prevailing standards to be able to account for the diversity in maternal experiences. Overall, the study advocates for a more inclusive approach to understanding the varied experiences of motherhood.